Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To solve the system of equations using substitution, follow these steps:
1. Write down the equations:
[tex]\[ \begin{array}{l} 2c - d = -2 \quad \text{(Equation 1)} \\ 4c + d = 20 \quad \text{(Equation 2)} \end{array} \][/tex]
2. Solve Equation 1 for [tex]\( d \)[/tex]:
[tex]\[ 2c - d = -2 \implies d = 2c + 2 \][/tex]
3. Substitute [tex]\( d = 2c + 2 \)[/tex] into Equation 2:
[tex]\[ 4c + (2c + 2) = 20 \][/tex]
4. Combine like terms:
[tex]\[ 4c + 2c + 2 = 20 \implies 6c + 2 = 20 \][/tex]
5. Solve for [tex]\( c \)[/tex]:
[tex]\[ 6c + 2 = 20 \implies 6c = 18 \implies c = 3 \][/tex]
6. Substitute [tex]\( c = 3 \)[/tex] back into the expression for [tex]\( d \)[/tex]:
[tex]\[ d = 2c + 2 \implies d = 2(3) + 2 \implies d = 6 + 2 \implies d = 8 \][/tex]
7. Write the solution as an ordered pair:
[tex]\[ (c, d) = (3, 8) \][/tex]
8. Verify the solution:
Substitute [tex]\( c = 3 \)[/tex] and [tex]\( d = 8 \)[/tex] back into the original equations to ensure both are satisfied:
- For Equation 1: [tex]\( 2(3) - 8 = 6 - 8 = -2 \)[/tex] (True)
- For Equation 2: [tex]\( 4(3) + 8 = 12 + 8 = 20 \)[/tex] (True)
Since both equations are satisfied, the solution to the system of equations is [tex]\( (3, 8) \)[/tex].
Therefore, the correct answer is:
[tex]\[ (3, 8) \][/tex]
1. Write down the equations:
[tex]\[ \begin{array}{l} 2c - d = -2 \quad \text{(Equation 1)} \\ 4c + d = 20 \quad \text{(Equation 2)} \end{array} \][/tex]
2. Solve Equation 1 for [tex]\( d \)[/tex]:
[tex]\[ 2c - d = -2 \implies d = 2c + 2 \][/tex]
3. Substitute [tex]\( d = 2c + 2 \)[/tex] into Equation 2:
[tex]\[ 4c + (2c + 2) = 20 \][/tex]
4. Combine like terms:
[tex]\[ 4c + 2c + 2 = 20 \implies 6c + 2 = 20 \][/tex]
5. Solve for [tex]\( c \)[/tex]:
[tex]\[ 6c + 2 = 20 \implies 6c = 18 \implies c = 3 \][/tex]
6. Substitute [tex]\( c = 3 \)[/tex] back into the expression for [tex]\( d \)[/tex]:
[tex]\[ d = 2c + 2 \implies d = 2(3) + 2 \implies d = 6 + 2 \implies d = 8 \][/tex]
7. Write the solution as an ordered pair:
[tex]\[ (c, d) = (3, 8) \][/tex]
8. Verify the solution:
Substitute [tex]\( c = 3 \)[/tex] and [tex]\( d = 8 \)[/tex] back into the original equations to ensure both are satisfied:
- For Equation 1: [tex]\( 2(3) - 8 = 6 - 8 = -2 \)[/tex] (True)
- For Equation 2: [tex]\( 4(3) + 8 = 12 + 8 = 20 \)[/tex] (True)
Since both equations are satisfied, the solution to the system of equations is [tex]\( (3, 8) \)[/tex].
Therefore, the correct answer is:
[tex]\[ (3, 8) \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.